EFFECTIVENESS OF USING THE SYSTEM OF BALANCED INDICATORS IN THE MANAGEMENT OF TEXTILE ENTERPRISES - Azimova Feruza Payzievna (Galaxy International Interdisciplinary Research Journal, 2022)
This article examines the issue of improvement in the management of textile enterprises based on the application of the balanced scorecard system.